Investigation of the relationship between the indicators of physical preparedness and the basic technique elements of young water-slalom athletes - Окунь, Дарья; Мулик, Екатерина (Slobozhanskyi Herald of Science and Sport, 2017)
Dar’ia Okun & Kateryna Mulyk Purpose: to determine the relationship between the indicators of physical fitness and the basic technical elements of young water-slalom athletes. Material & Methods: theoretical analysis and generalization of data from scientific and methodological literature, pedagogical control tests (tests), methods of mathematical statistics. Results: it found to achieve successful results in water-slalom, the level of development of motor qualities is of great importance. It identified the most important lessons for the water-slalom motor quality (speed-strength, power). Conclusion: during preparation of athletes in water-slalom, in the first place, these motor qualities must be taken into account.